The Effect of Technology on Sustainable Architectural Buildings (Journal of Architectural Design, 2023)
Being indispensable for improvement and progress, sustainable architectural development as a process is the base of overcoming environmental shortcomings and enhancement of environmental conditions. Moderate progress must be driven by sustainability especially in under-development countries. Development of sustainable man-made environment is usually considered as sustainable architect. Sustainable architect building is not a new conceptualization of deconstruction or modernism, rather this is the thought process to design architect in harmony with nature. Building and architect are not the whole eco-system, but are small incorporated sections of life cycle. Quality of interior space and people become more significant in design of eco-tech architecture. This paper aims to discover impact of technology on sustainable architect building. As, sustainable architecture building is itself a technology. This study demonstrates the impact of architect on nature. It also highlights the integration of ecotechnology designs and sustainable architect